Equilibrium unemployment with outsourcing under labour market imperfections - Erkki Koskela; Rune Stenbacka (Center for Economic Studies and ifo Institute (CESifo), 2007)
We study the various consequences of and the incentives for outsourcing. We argue that the wage elasticity of labour demand increases as a function of the share of outsourcing, which is a result consistent with existing empirical research. Furthermore, we show that a production mode with a higher proportion of outsourcing activity reduces the negotiated wage in the high-wage country with an imperfectly competitive labour market so that outsourcing reduces equilibrium unemployment. Finally, we characterize the optimal production mode and show that stronger labour market imperfections lead to a production mode with a higher share of outsourcing.
Keywords: E23; E24; J51; J64; 330; Arbeitslosigkeit; Outsourcing; Lohnverhandlungen; Unvollkommener Markt; Arbeitsmarkttheorie; Theorie